2018
DOI: 10.1073/pnas.1721930115
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filament accumulation can stabilize microtubules inCaenorhabditis elegansmotor neurons

Abstract: Neural circuits utilize a coordinated cellular machinery to form and eliminate synaptic connections, with the neuronal cytoskeleton playing a prominent role. During larval development of , synapses of motor neurons are stereotypically rewired through a process facilitated by dynamic microtubules (MTs). Through a genetic suppressor screen on mutant animals that fail to rewire synapses, and in combination with live imaging and ultrastructural studies, we find that intermediate filaments (IFs) stabilize MTs to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…It has been shown recently in C . elegans that IFs hyperstabilize MTs to prevent synapse rewiring consistent with the idea that IF levels are directly associated with axonal MT stability . Importantly, organelle transport is largely affected by IFs such as vimentin in non‐neuronal cells, and in neurons the transport of NF subunits are tightly coordinated by kinesin‐1 (anterograde direction) and dynein (retrograde direction) .…”
Section: Introductionsupporting
confidence: 74%
“…It has been shown recently in C . elegans that IFs hyperstabilize MTs to prevent synapse rewiring consistent with the idea that IF levels are directly associated with axonal MT stability . Importantly, organelle transport is largely affected by IFs such as vimentin in non‐neuronal cells, and in neurons the transport of NF subunits are tightly coordinated by kinesin‐1 (anterograde direction) and dynein (retrograde direction) .…”
Section: Introductionsupporting
confidence: 74%
“…On the other hand, the MT fragmentation along the axons could be connected to the already known action of some anti-cancer drugs, which exerted adverse effects on the peripheral nervous system in clinical studies, with documentation of degeneration and fragmentation of sensory axons, reduced axonal length and also reduced axonal transport in animal models [77]. Interestingly, it has recently been reported that intermediate filament accumulation directly alters MT stability in motor neurons in Caenorhabditis elegans [78]. Kurup and colleagues showed for the first time that the genetic loss or the pharmacological disruption of the essential intermediate filament network was sufficient to shift the MT balance from stable to dynamic, participating in the regulation of axonal transport, from which synapse rewiring depends in C. elegans.…”
Section: Discussionmentioning
confidence: 99%
“…This recently developed method has been used to degrade several endogenously tagged GFP fusion proteins, revealing loss-of-function phenotypes (Chuang et al 2014;Wang et al 2017b;Kim et al 2018;Kurup et al 2018). Degradation of proteins to a level below detection can be accomplished and occurs quickly, although at least one abundantly expressed protein could not be depleted entirely using this method (Wang et al 2017b).…”
Section: Experimental Considerationsmentioning
confidence: 99%